2017
DOI: 10.14740/jocmr3117w
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Toxoplasma gondii Infection Markers Among Heterosexual Couples

Abstract: BackgroundVery little is known about concordance of Toxoplasma gondii (T. gondii) infection markers among couples. Through a cross-sectional study, we sought to determine the correlation of T. gondii infection in a sample of 119 heterosexual couples in Durango State, Mexico.MethodsParticipants were examined for the presence of anti-T. gondii IgG and IgM antibodies using enzyme-linked immunoassays. IgG and IgM seropositive couples were further analyzed for the presence of T. gondii DNA by using polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A study showed that transmission of T. gondii through the sexual route did not have epidemiological significance for men and animals [44]. In another study, a poor concordance of serological and molecular markers of T. gondii infection among heterosexual couples was found [45]. In contrast, a study showed that female sex workers had a higher seroprevalence of T. gondii infection than their controls, and injuries during sex work were associated with T. gondii seropositivity [22].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that transmission of T. gondii through the sexual route did not have epidemiological significance for men and animals [44]. In another study, a poor concordance of serological and molecular markers of T. gondii infection among heterosexual couples was found [45]. In contrast, a study showed that female sex workers had a higher seroprevalence of T. gondii infection than their controls, and injuries during sex work were associated with T. gondii seropositivity [22].…”
Section: Discussionmentioning
confidence: 99%